Effects of Implementing a Routine Postpartum Fasting Blood Glucose on the Completion of the Gold Standard 2-Hour Oral Glucose Tolerance Test in Gestational Diabetics - Prior, Alissa K.; Dolin, Cara D.; Bender, Whitney; Durnwald, Celeste P.; Hamm, Rebecca F. (American Journal of Perinatology, 2024)
Objective Rates of completion of the gold standard 2-hour oral glucose tolerance test (OGTT) for impaired glucose intolerance postpartum in patients with gestational diabetes mellitus (GDM) are consistently less than 50%. Screening tests performed prior to hospital discharge, including fasting blood glucose (FBG) to detect persistent hyperglycemia, have been investigated. We lack evidence, however, on whether implementation of routine postpartum FBG impacts the likelihood of obtaining the routine 2-hour OGTT. We sought to retrospectively compare the rates of completion of the 2-hour OGTT pre- and postimplementation of a routine FBG screen.Study Design We performed a single-center retrospective cohort study comparing the completion of the 2-hour OGTT pre- and postimplementation of a routine FBG screen. Our primary outcome was the completion of the postpartum OGTT. Bivariate analyses assessed associations between demographic and preinduction clinical characteristics by pre- and post-implementation groups, as well as OGTT completion. Multivariable logistic regression was used to control for possible confounders. A sensitivity analysis was performed to account for the overlap with the coronavirus disease 2019pandemic.Results In total, 468 patients met the inclusion and exclusion criteria. In our post-intervention group, 64% of patients completed a postpartum FBG. For our primary outcome, completion of the 2-hour OGTT significantly decreased in our postintervention group from 37.1 to 25.9% (p = 0.009), adjusted odds ratio (aOR): 0.62, confidence interval (CI): 0.41–0.92. This difference was no longer statistically significant when excluding patients during the pandemic, from 40.3 to 33.1% (p = 0.228), aOR: 0.76, CI: 0.455–1.27.Conclusion Implementation of a routine FBG was associated with a negative impact on patients completing a 2-hour OGTT. The difference was no longer significant when excluding patients who would have obtained the OGTT during the pandemic, which may have been due to the smaller cohort. Future work should investigate patient perceptions of the FBG and its impact on their decision-making around the OGTT.Key Points
Keywords: COVID-19; fasting blood glucose; gestational diabetes; implementation; oral glucose tolerance test; pandemic; postpartum screening